2010
DOI: 10.1111/j.1468-1331.2010.02951.x
|View full text |Cite
|
Sign up to set email alerts
|

EFNS guidelines on the use of neuroimaging in the management of motor neuron diseases

Abstract: Background and purpose: These European Federation of Neurological Societies guidelines on neuroimaging of motor neuron diseases (MNDs) are designed to provide practical help for the neurologists to make appropriate use of neuroimaging techniques in patients with MNDs, which ranges from diagnostic and monitoring aspects to the in vivo study of the pathobiology of such conditions. Methods: Literature searches were performed before expert members of the Task Force wrote proposal. Then, consensus was reached by ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 122 publications
(246 reference statements)
5
66
0
2
Order By: Relevance
“…The recommendations are summarized in the EFNS guidelines [Filippi et al 2010]. Here, advanced neuroimaging techniques such as volumetric analyses, DTI, MRS, or (rs-)fMRI do not have a role yet in the diagnosis or routine monitoring of MNDs (class IV, level GCPP).…”
Section: Future Perspectives: Preparing For Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recommendations are summarized in the EFNS guidelines [Filippi et al 2010]. Here, advanced neuroimaging techniques such as volumetric analyses, DTI, MRS, or (rs-)fMRI do not have a role yet in the diagnosis or routine monitoring of MNDs (class IV, level GCPP).…”
Section: Future Perspectives: Preparing For Clinical Trialsmentioning
confidence: 99%
“…The European Federation of Neurological Societies (EFNS) guidelines on neuroimaging of MNDs (which were designed to provide practical help for neurologists to make appropriate use of neuroimaging techniques in patients with MNDs) are focused on MRI-based neuroimaging techniques [Filippi et al 2010]. For standard conventional MRI techniques, the following two basic recommendations are given.…”
Section: Magnetic Resonance Imaging Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…"the specific search for these abnormalities for the purpose of making a firm diagnosis of ALS is not recommended" 1 .…”
Section: Original Articlementioning
confidence: 99%
“…Proton magnetic resonance spectroscopy (MRS) studies have consistently shown evidence of neuronal dysfunction in the primary motor cortex (PMC) of ALS (Filippi et al 2010). However, no consensus has been reached on the standard protocols for performing MRS scans in ALS.…”
Section: Introductionmentioning
confidence: 99%